Communication And The Mediating Effect Of Team Work On Smile Autoservice - Marjuni, Imran; Payangan, Otto R.; Sobarsyah, Sobarsyah (YUME : Journal of Management, 2024)
This study aims to determine the effect of communication on employee performance through team work mediation at Smile Auto Service Makassar, which is one of the largest private companies in the Makassar area. The research design used uses a quantitative research approach to examine an individual in a group using the path analysis method with the help of SPSS 26. In this research, the population collection technique uses a saturated sampling technique with a sample size of 30 people. The results of this research show that communication has a positive and significant effect on team work, communication has a positive and significant effect on employee performance, team work has a positive and insignificant effect on employee performance and communication through team work mediation has a positive and insignificant effect, so it can be said that team work has not been able to become a mediating variable in this research. Kata Kunci: Communication, Team Work and Employee Performance.